COVID-19 and diabetes mellitus: A need for prudence in elderly patients from a pooled analysis. Issue 4 (July 2020) - Desai, Rupak; Singh, Sandeep; Parekh, Tarang; Sachdeva, Sonali; Sachdeva, Rajesh; Kumar, Gautam
Abstract: Objective: The objective of this study was to evaluate the pooled estimate of diabetes prevalence in young (<50 years) versus elderly (>50 years) COVID-19 cohorts. Methods: Studies published between December-2019 and March-2020 reporting demographic and clinical characteristics of COVID-19 cases were identified. A total of 11 studies included accounting for 2084 COVID-19 patients. Results: The overall prevalence of diabetes in COVID-19 patients with a mean age>50 years was 13.2%, whereas studies with relatively younger patients (mean age <50 years) had a pooled prevalence of 9.0% Conclusion: The overall prevalence of diabetes in COVID-19 patients was found to be 13.2% with studies including relatively elderly patients showing higher rates of diabetes. The intermingled effects of diabetes with other cardiovascular comorbidities warrant age-specific outcomes data including the impact of ongoing antidiabetic treatment. Highlights: Eleven studies included accounting for 2084 COVID-19 patients. The overall prevalence of diabetes in elderly COVID-19 cohort (mean age>50 yrs) was 13.2%. Relatively younger COVID-19 cohort (mean age <50 yrs) had a pooled prevalence of 9.0%. The prevalence of diabetes in elderly COVID-19 patients remain significantly higher. The intermingled effects of diabetes with cardiovascular comorbidities warrant age-specific outcomes data.